ANALISIS KINERJA KEUANGAN BERDASARKAN METODE DOUBLE DISTRIBUTION DAN ACTIVITY BASED COSTING DI RSUP. PROF. DR. R. D. KANDOU MANADO (STUDI KASUS DI INSTALASI CARDIO VASCULAR DAN BRAIN CENTER) - Pessak, Donald R. M.; Saerang, David P. E.; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2023)
This study aims to determine kece slot the Financial Performance Analysis Based on the Double Distribution Method and Activity Based Costing in RSUP. Prof. Dr. R. D. Kandou Manado (Case Study at the Cardio Vascular and Brain Center Installation).This study used qualitative research with a case study approach. Data obtained by in-depth interview techniques. Informants in this study were coordinators, sub-coordinators and heads of the Cardio Vascular Installation and Brain kece slot Center with the consideration that they are the parties who own and provide information about the things being studied. Calculation of the cost of medical action using the Double Distribution method at the Cardio Vascular and Brain Central Installation of Prof. Dr.R. D Kandou General Hospital Manado tends to be under cost compared to the Activity Base d Costing method. In the case of determining the cost is too low, Prof. Dr. R. D Kandou Manado General Hospital tends to experience losses so it is necessary to increase the determination of rates up to 16.07% in accordance with the difference between the Double Distribution method and the Activity Based Costing method kece slot which is expected with this strategy will have an impact on reducing losses (deficits) and even obtaining profits in operational activities. on the ratio of liquidity, solvency, profitability and activity ratio. In terms of liquidity ratios, the use of the Double Distribution method is better than the Activity Based Costing method, while for solvency ratios, profitability and activity ratios the best is to use the Activity Based Costing method.